Vaccination perspectives among adolescents and their desired role in the decision-making process - Rachel Herman; Louise-Anne McNutt; Mehek Mehta; Daniel A. Salmon; Robert A. Bednarczyk; Jana Shaw (Taylor & Francis Group, 2019)
Background: To assess the knowledge and attitudes of middle school students toward vaccination, we measured their understanding of vaccine safety and effectiveness, expectations for communication with heath care providers, and their desired role in the vaccination decision-making process. Methods: A cross-sectional, self-administered survey was conducted among seventh and eighth grade students in a middle school in Upstate New York. Bivariate analyses were conducted to identify differences in perspective by gender, grade, and attitudes toward vaccination. Results: Of 346 students attending class, 336 (97.1%) participated. The majority of respondents were White (71.3%) and 11 to 13 years of age (78.2%). Boys were significantly more likely than girls to perceive vaccines to be very safe (48.4% vs 30.2%, p < 0.01) and very effective (49.7% vs 29.0%, p < 0.01). Approximately one-third of adolescents reported having a say in the decision to be vaccinated and a quarter of students expressed a desire for specific information about vaccines. Conclusions: This study found that young adolescents in a nonurban area of Upstate New York were generally marginalized in the vaccine decision-making process yet third of them indicated an interest in how vaccines work and a desire to participate in healthcare decisions. Interventions to improve vaccine uptake among adolescents should capitalize on this desire to understand vaccine safety, effectiveness and mechanism of action.